RANCANGAN DRAFT EVALUASI PROGRAM TELEVISI LOKAL DALAM EDUKASI KONSERVASI BUDAYA KALIMANTAN BARAT - Egy Abdi; Indri Astuti; Afandi Afandi (Jurnal Pustaka Komunikasi, 2023)
The existence identification of local television as the mainstream media in cultural conservation education that did not apply systemic and scientific program evaluation is problematic which had implications for hampering the level of program progressivity, local television stations, and fulfilling the rights of local communities to obtain information with higher quality content. The purpose of this study was to design a draft evaluation for local television programs specifically for the Warta Citizen Journalism program at Television Ruai Pontianak used the CSE-UCLA evaluation model. This research used the Research and Development (RD) method. The result of the research was the production of a local television program evaluation draft consisting of a general detailed narrative of the program referring to the CSE UCLA evaluation component namely system assessment, planning, implementation, implementation, development and program certification as evaluation material that can be used by assessors given authority by the party. company, in addition to involving other information deemed relevant. This study also produced an assessment instrument in the form of an evaluation questionnaire specially designed for assessors who are representative parties in all entities related to broadcasting, starting from educators, cultural figures, indigenous peoples, viewers and non-viewers of Ruai TV, to civil society in carrying out the assessment. critical and objective.